2004
DOI: 10.1063/1.1772758
|View full text |Cite
|
Sign up to set email alerts
|

Modulated hydrogen beam study of adsorption-induced desorption of deuterium from Si(100)-3×1:D surfaces

Abstract: We have studied the kinetic mechanism of the adsorption-induced-desorption (AID) reaction, H+D/Si(100) --> D2. Using a modulated atomic hydrogen beam, two different types of AID reaction are revealed: one is the fast AID reaction occurring only at the beam on-cycles and the other the slow AID reaction occurring even at the beam off-cycles. Both the fast and slow AID reactions show the different dependence on surface temperature Ts, suggesting that their kinetic mechanisms are different. The fast AID reaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Their results are in agreement with ours made by RF-IGC method, at higher time values and after  = 1, at saddle-points positions. Thus, desorption at higher time values outcomes from these islands due to steric effects between the nearest of them [27], without high energy demands.…”
Section: Statue L351 a Pure Dolomite From The Interior Of The Archaementioning
confidence: 99%
“…Their results are in agreement with ours made by RF-IGC method, at higher time values and after  = 1, at saddle-points positions. Thus, desorption at higher time values outcomes from these islands due to steric effects between the nearest of them [27], without high energy demands.…”
Section: Statue L351 a Pure Dolomite From The Interior Of The Archaementioning
confidence: 99%
“…Incident H atoms break DSi-SiD bonds to form four neighboring dideuterides (dihydrides), i.e., a local (1 · 1) phase, which is thermodynamically unstable on the (3 · 1) domains distributed on the (2 · 1) monodeuteride surface [17]. The instability of such a local (1 · 1) dideuteride phase accompanies recombinative desorption of a molecule to return to the (3 · 1) phase, leaving behind a dangling bond [15,16]. To understand detailed kinetic mechanism the O-induced D 2 desorption should be studied comparatively with the H-induced D 2 one [18].…”
Section: Introductionmentioning
confidence: 99%
“…The recent progress in the study of the H-induced D 2 desorptions from D-terminated Si(1 0 0) surfaces shows up that the desorption is induced by adsorption of H atoms onto a (3 · 1) monodeuteride/dideuteride domain on the (2 · 1) monodeuteride Si surfaces [15,16]. In a (3 · 1) phase the rows of dideuterides (DSiD) and monodeuterides (DSiSiD) are alternately arranged.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of pub- lished papers, we suggested that the hot atom mechanism is ruled out on the basis of several experimental facts: ͑i͒ the unexpectedly high reaction order for the HD ͑approximately second-order͒ and D 2 ͑approxi-mately fourth-order͒ desorptions; 8 ͑ii͒ the strong temperature dependence of efficient D 2 desorption; 9 and ͑iii͒ the efficient adsorption of H atoms even onto D-terminated Si atoms. 10 To reconcile these facts we have proposed a hot complex mechanism by which H atoms are first bound in the excited states of chemisorption in a DSi-SiD unit. 9,11 As evidenced by the efficient formation of dihydrides, 10 the reaction of H atoms with terminated Si atoms is one of the most important energy dissipation channels when H atoms are trapped on a Si surface.…”
mentioning
confidence: 99%
“…10 To reconcile these facts we have proposed a hot complex mechanism by which H atoms are first bound in the excited states of chemisorption in a DSi-SiD unit. 9,11 As evidenced by the efficient formation of dihydrides, 10 the reaction of H atoms with terminated Si atoms is one of the most important energy dissipation channels when H atoms are trapped on a Si surface. This energy dissipation should be seriously taken into account when the hopping of hot H atoms across D-terminated Si͑100͒ surfaces is treated.…”
mentioning
confidence: 99%